Persepsi Mahasiswa Sosiologi Fakultas Ilmu Sosial dan Politik Universitas Hasanuddin Angkatan 2021-2023 terhadap Akses dan Kualitas Sumber Daya Pembelajaran - Setiawan, Zahra Apriliani; Wahyu; Sala; Rafli (Department of Sociology Faculty of Social and Political Sciences, 2024)
ABSTRACT This study aims to analyze the perceptions of Sociology students from the Faculty of Social and Political Sciences, Hasanuddin University (2021–2023 cohorts), regarding access to and the quality of learning resources. Despite the significant progress in higher education in Indonesia, inequalities in access and quality remain a major challenge, particularly for students from lower socio-economic backgrounds. This research employs a descriptive quantitative method, with data collected through an online survey involving 64 randomly selected respondents. The findings reveal disparities in accessing educational facilities and the adequacy of teaching quality. Furthermore, economic limitations and insufficient institutional support exacerbate students' learning experiences. Using Pierre Bourdieu’s theory of social practice, this study explains how economic, social, and cultural capital influence students’ perceptions within the educational arena. These findings provide recommendations for educational institutions to develop more inclusive policies and improve the quality of higher education services. Keywords: Higher Education, Student Perception, Access to Education, Quality of Learning Resources ABSTRAK Penelitian ini bertujuan untuk menganalisis persepsi mahasiswa Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin angkatan 2021-2023 terhadap akses dan kualitas sumber daya pembelajaran. Meskipun pendidikan tinggi di Indonesia terus berkembang, ketimpangan akses dan kualitas pendidikan masih menjadi tantangan, terutama bagi mahasiswa dari latar belakang sosial-ekonomi rendah. Penelitian ini menggunakan metode deskriptif kuantitatif dengan data yang diperoleh melalui survei daring kepada 64 responden yang dipilih secara acak. Hasil penelitian menunjukkan bahwa mahasiswa menghadapi kesenjangan dalam mengakses fasilitas pendidikan dan kualitas pengajaran yang memadai. Selain itu, keterbatasan ekonomi serta kurangnya dukungan institusi memperburuk pengalaman belajar mahasiswa. Dengan menggunakan teori praktik sosial Pierre Bourdieu, penelitian ini menjelaskan bagaimana modal ekonomi, sosial, dan budaya mempengaruhi persepsi mahasiswa dalam arena pendidikan. Temuan ini memberikan rekomendasi bagi institusi pendidikan untuk mengembangkan kebijakan yang lebih inklusif dan meningkatkan kualitas layanan pendidikan tinggi. Kata Kunci: Pendidikan Tinggi, Persepsi Mahasiswa, Akses Pendidikan, Kualitas Sumber Daya Pembelajaran.